Foreign Exchange Inflows in Emerging Markets: How Much are they Sterilised?. (26th February 2016) - Bleaney, Michael; Devadas, Sharmila
Abstract : As some emerging market economies have amassed large quantities of foreign exchange reserves, concern has arisen over the sterilisation of the domestic money stock from these flows. Existing studies focus mostly on narrow (reserve) money, and estimate a high degree of sterilisation. Empirical work on the long‐run relationship between money and prices emphasises broad money, yet the long‐run effect of foreign exchange inflows on broad money has been almost entirely ignored. Using a sample of quarterly data from 28 countries over the period 1990–2010, it is shown that broad money is sterilised to a significantly smaller degree than reserve money, raising concerns about the implications for financial imbalances and inflation. This pattern of sterilisation is not confined to any particular group of countries and is unrelated to the nature of the flows (e.g. current account versus capital account surpluses). Sterilisation rates have increased in Asia during the recent period of persistent accumulation of foreign exchange reserves.